1967
DOI: 10.1021/ja00981a002
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Formation of Free Radicals from Aliphatic Amines as Studied by Electron Spin Resonance

Abstract: Electron spin resonance studies of ultraviolet-irradiated CH3NH2, CD3NH2, (CH3)2NH, (CH3)2ND, (CD3)2NH, and (CH3)3N have been made at 77 °K. The primary processes established are CH3NH2 + hv ->-H• + CH3NH, (CH3)2NH + hv H + (CH3)2N •, and (CH3)3N + hv -* • CH3 + (CH3)2N•. Studies of solutions of H202 in CH3NH2 and in CD3NH2 irradiated at 77 °K were also made and the secondary reaction established is OH + CH3NH2 -* H20 + CH3ÑH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Free radical formation from aliphatic amines has been investigated previously by a number of methods. For studies of the solid state, electron spin resonance was used to observe radical species produced by X-rays (3) and y-radiolysis (4-6) in single crystals or by uv photolysis (7,8) in frozen glasses. Optical absorption was used to follow the radicals produced by pulse radiolysis (9)(10)(11)(12) in aqueous solutions that were saturated with N 2 0 to convert ePa,.…”
Section: Andh~-(ch~)-~~h~-(ch~)~-~~h~) Etc Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radical formation from aliphatic amines has been investigated previously by a number of methods. For studies of the solid state, electron spin resonance was used to observe radical species produced by X-rays (3) and y-radiolysis (4-6) in single crystals or by uv photolysis (7,8) in frozen glasses. Optical absorption was used to follow the radicals produced by pulse radiolysis (9)(10)(11)(12) in aqueous solutions that were saturated with N 2 0 to convert ePa,.…”
Section: Andh~-(ch~)-~~h~-(ch~)~-~~h~) Etc Asmentioning
confidence: 99%
“…N-centered radicals were also formed by ultraviolet irradiation of glassy samples of mono-, di-, and trialkyl amines at low temperatures (7,8). However, in the reaction of OH radicals with aliphatic amines in aqueous solution (9)(10)(11)(12)(13)(14)17), H-abstraction from the nitrogen as well as from the carbon adjacent to it occurred in alkaline medium.…”
Section: Andh~-(ch~)-~~h~-(ch~)~-~~h~) Etc Asmentioning
confidence: 99%
“…The spectrum of this radical, shows a main septet with a splitting of 28.0 G and an external satellite line (1,2). This spectrum has been interpreted in terms of equal, isotropic, proton and nitrogen splitting constants (1).…”
Section: Methodsmentioning
confidence: 92%
“…The field sweep calibration was carried out by a Mn2+ irradiation in the solid state (1)(2)(3)(4). The low doped sample of MgO (5).…”
mentioning
confidence: 99%
“…It is part of our systematic investigation on radicals containing one nitrogen atom, such as NH 2 [ 12], H 2 CN [9], (CH 2 )zN, (CH 2 )zNH+, and the cyclic compounds C 3 H 6 N and C 3 H 6 NH + [ 10]. The first investigation on the neutral compound (CH 3 hN was carried out by Hadly and VoJman [ 13] who concluded that the unpaired electron resides in a sp 3 hybrid orbital, based on the large isotropic hfcc's measured for the nitrogen center ( 32 G). Different results were reported by Danen and Kensler [ 14] who observed a far smaller isotropic hfcc ( 14.78 G) for the nitrogen center.…”
Section: Introductionmentioning
confidence: 99%